Material flow analysis and characteristics of multiple-source organic solid wastes from a perspective of ecological network analysis A case study in Hefei, China - Zhang, Yulin (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2023)
The numerous resources are consumed and a large number of multiple-source organic solid wastes are discharged during urban metabolic, which put pressures to environment. This study combined material flow analysis and ecological network analysis to comprehensively analyse the metabolism of multiple-source organic solid waste in Hefei. Analysing current metabolic characteristics of urban multiple-source organic solid waste and relationships between the components of metabolic system can help urban environmental management. The internal material flows of the system were analysed by a metabolic network containing 5 nodes and 18 pathways, which revealed metabolic characteristics of multiple-source organic solid waste in Hefei. The study showed that the metabolic system of multiple-source organic solid waste was relatively stable though distribution of internal flows changed in 8 years. The metabolic environment and agricultural sector covered a relatively large weight in this model. The control and exploitation relationships dominated the metabolic system. The urban metabolic mechanism reflected in this research can improve efficiency of urban metabolic resource, optimize waste management and provide data support for sustainable urban development. This study provided scientific guidance for metabolic research in Hefei and similar cities in China's rapid economic development